Evaluation of nasal obstruction in nasal septum deviations using objective and subjective methods: Evaluation of nasal obstruction in nasal septum deviations - Akpinar, Meltem; Saatci, Ozlem; Celik, Metin (Journal of Surgery and Medicine, 2026)
Background/Aim: Nasal septum deviation (NSD) is a prevalent cause of nasal obstruction, significantly impairing quality of life. Although various subjective and objective assessment tools exist, the correlation between these methods remains insufficiently investigated. This study aimed to evaluate the relationship between septal deviation morphology and peak nasal inspiratory flow (PNIF) measurements, and to determine the correlation between objective PNIF values and subjective Nasal Obstruction Symptom Evaluation (NOSE) scores. Methods: Between July and September 2023, 52 patients diagnosed with NSD and nasal obstruction, along with 20 healthy controls, were enrolled. Patients were classified into three groups (A, B, and C) based on the degree of nasal obstruction. PNIF measurements and NOSE scores were obtained from all participants. Results: The mean NOSE score and PNIF value in the study group were 59.33 (27.19) and 76.73 (38.76) l/min, respectively, while the mean PNIF value in the control group was 145.5 (17.01) l/min. Statistically significant differences were found in PNIF and NOSE scores between groups. A strong correlation was observed between PNIF and NOSE scores (P=0.004). Conclusion: The combined use of objective PNIF measurements and subjective NOSE assessments offers a comprehensive evaluation of nasal obstruction due to septal deviation, improving diagnostic accuracy and clinical decision-making.